Measuring zygomaticomaxillary complex symmetry three-dimensionally with the use of mirroring and surface based matching techniques. Issue 10 (October 2016) - Ho, Jean Pierre T.F.; Schreurs, Ruud; Milstein, Dan M.J.; Dubois, Leander; Maal, Thomas J.J.; de Lange, Jan; Becking, Alfred G.
Abstract: Objective: The study aim was to validate a new method for measuring zygomaticomaxillary complex (ZMC) symmetry, which can be helpful in analyzing ZMC fractures. Methods: Three-dimensional virtual hard-tissue models were reconstructed from computed tomography (CT) datasets of 26 healthy individuals. Models were mirrored and superimposed. Absolute average distance (AD) and 90th percentile distance (NPD) were used to measure overall and maximal symmetry. The Intraclass Correlation Coefficient (ICC) was calculated to measure interobserver consistency. In order to determine whether this technique is applicable in ZMC fracture cases, 10 CT datasets of individuals with a unilateral ZMC fracture were analyzed. Results: For the unaffected group the mean AD was 0.84 ± 0.29 mm (95% CI 0.72–0.96) and the mean NPD was 1.58 ± 0.43 mm (95% CI 1.41–1.76). The ICC was 0.97 (0.94–0.98 as 95% CI), indicating almost perfect interobserver agreement. In the affected group the mean AD was 2.97 ± 1.76 mm (95% CI 1.71–4.23) and the mean NPD was 6.12 ± 3.42 mm (95% CI 3.67–8.57). The affected group showed near-perfect interobserver agreement with an ICC of 0.996 (0.983–0.999 as 95% CI). Conclusions: The method presented is an accurate instrument for evaluation of ZMC symmetry, which can be helpful for advanced diagnostics and treatment evaluation.